Vocabulary Learning Strategies in Second Language Acquisition: A Critical Synthesis of Theory, Research, and Pedagogical Implications - Mal, Ahsanullah; Nayak, Fridullah (Politeknik Siber Cerdika Internasional, 2025)
The acquisition of vocabulary occupies a central position in second language acquisition (SLA), as lexical knowledge underpins communicative competence across all four language skills. Despite this recognition, vocabulary learning strategies (VLS) remain an area where pedagogical practice has often lagged behind theoretical understanding. This critical review synthesizes empirical research and theoretical perspectives on VLS within SLA, drawing upon a purposive corpus of six scholarly works that collectively span questions of strategy taxonomy, individual learner differences, contextual influences, technology integration, and the instructor-learner belief gap. The review is organized around a person-task-context-strategy tetrahedral model that positions vocabulary acquisition as a dynamic, interactional process rather than a discrete cognitive event. Findings indicate that no single strategy constitutes an optimal solution for all learners; rather, the effectiveness of any given strategy is contingent upon the learner's proficiency level, motivational orientation, metalinguistic awareness, cultural background, and the specific demands of the learning task. Metacognitive and cognitive strategies consistently emerge as the most frequently employed by effective learners, while affective and social strategies remain systematically underutilized. The review further establishes that technology-enhanced vocabulary learning offers substantive gains, particularly when digital tools are employed with pedagogical intentionality and explicit instruction. Critical analysis reveals persistent methodological limitations in existing research, including overreliance on self-report questionnaires, limited longitudinal designs, and insufficient attention to contextual variables. Pedagogical implications are offered for instructors seeking to bridge the gap between strategy theory and classroom practice. The review concludes by identifying priority areas for future empirical investigation, including the effectiveness of strategy instruction models, the role of learner autonomy in digital learning environments, and the interplay between cultural learning traditions and strategy preference.